PENGARUH JUMLAH KUNJUNGAN WISATAWAN, JUMLAH OBYEK WISATA DAN PENDAPATAN PERKAPITA TERHADAP PENERIMAAN SEKTOR PARIWISATA DI KABUPATEN KUDUS - Nadia Rahma, Femy; Retno Handayani, Herniwati (Diponegoro Journal of Economics, 2013)
During 1997-2011 being known that rate of tourism sector acceptance in Kudus Distric during the latest fifteen years always increase, however the percentage of realization the acceptance of tourism sector has been always fluctuated from the determined target, so it needs to be analyzed some factors that influence the acceptance of tourism sector in Kudus District.This study aimed to analyze the influence of the variable Number of Tourist Arrivals, Tousrist Attractions, and a per capita income of the Tourism Sector in the Kudus District Government. The data of this study is secondary data in the from of Â chronological order (time series). The analytical tool used in this study is multiple linear regression with the reception area of the Tourism Sector as the dependent variable and three independents variables are a variable number of tourists arrival, tourism attraction, and income per capita.Partially, the number of tourist, the number of attraction of tourism variable, and variable income percapita has a significant effect. And from the three variable is the most dominant influence on acceptance of tourism sector in Kudus District is the number of tourism variable.Â